A Test of Uncovered Interest Rate Parity for Ten European Countries Based on Bottstrapping and Panel Data Models - Tom Bernhardsen (Norges Bank, 1997)
Based on both single country models and panel data models uncovered interest rate parity is tested for ten European countries relative to Germany by regressing exchange rate changes on interest rate differentials. The period is from March 1979 to February 1996 at one month, three, six and twelve months maturity. Since exchange rate changes follow a non-normal distribution, the distribution of the test-statistic is bootstrapped from the sample. The bootstrapped confidence intervals are wider with larger upper limits than the confidence intervals based on the normal distribution. The regression coefficients, all estimated to be less than one, are considerably lower for long term maturities than for short term maturities, and lower for countries outside the ERM than for ERM countries. This is explained by differences in the variance of exchange rate changes and thereby by the risk premium between long and short term maturities and the risk premium between these two groups of countries.
hdl:11250/2500578
Keywords: C32; E43; 330; uncovered interest rate parity; interest rate differentials; risk premium; bootstrapping; panel data models